2019
DOI: 10.1186/s12894-019-0533-x
|View full text |Cite
|
Sign up to set email alerts
|

Cost comparison between open radical cystectomy, laparoscopic radical cystectomy, and robot-assisted radical cystectomy for patients with bladder cancer: a systematic review of segmental costs

Abstract: BackgroundRobot-assisted radical cystectomy is becoming a common treatment for bladder carcinoma. However, in comparison with open radical cystectomy, its cost-effectiveness has not been confirmed. Although few published reviews have compared total costs between the two surgical procedures, no study has compared segmental costs and explained their impact on total costs.MethodsA systematic review was conducted based on studies on the segmental costs of open, laparoscopic, and robot-assisted radical cystectomy u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Increasing uptake of RARC may have cost implications, which we have not explored thoroughly in this study. Published systematic review analyses have concluded RARC may be cost‐effective compared to ORC 35 . Cost factors involved are predominantly based on equipment and operating room costs, length of stay, transfusion‐related requirements, complications, and readmission‐related expenditure 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing uptake of RARC may have cost implications, which we have not explored thoroughly in this study. Published systematic review analyses have concluded RARC may be cost‐effective compared to ORC 35 . Cost factors involved are predominantly based on equipment and operating room costs, length of stay, transfusion‐related requirements, complications, and readmission‐related expenditure 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The operative time, instruments used, length of hospital stay, and the numbers of annual cases were key drivers of costs. The results from the segmented costs indicated that RARC operating costs were higher and accounted for the largest proportion of total RARC costs [6]. The cost of endostapling devices makes RARC more expensive.…”
Section: Discussionmentioning
confidence: 99%
“…Robot-assisted radical cystectomy (RARC) is more expensive than open radical cystectomy [6]. One of the additional costs is due to the use of staples in ileo-ileal anastomoses.…”
Section: Introductionmentioning
confidence: 99%
“…For this study, participating surgeons must have completed at least 30 procedures of each, which will be close to the plateau of their learning curves. The study will report on oncological, perioperative, functional, and cost outcomes for RARC with ICUD and hopefully make a major contribution to the literature, potentially resolving some outstanding areas of doubt in the argument for RARC and ICUD vs. the open approach [27] .…”
Section: Trialsmentioning
confidence: 99%